In search of socially responsible investors: a Latent Profile Analysis - Robba, Matteo; Sorgente, Angela; Iannello, Paola (Frontiers in Behavioral Economics, 2024)
Introduction Socially responsible investments (SRI) increased their popularity among investors over the last two decades. However, there is still a lack of knowledge on socially responsible investors' characteristics and motivations behind the decision to invest in SRI. The present paper aims at filling this gap by profiling current and potential sustainable investors. Method Cross-sectional data from a representative sample of Italian consumers (N = 1,002) was used to perform a Latent Profile Analysis (LPA), a clustering technique, and identify various sub-groups within the respondents. Subsequently, chi-square test and one-way ANOVA were performed to determine which profile(s) was mostly associated with current and potential socially responsible investing. Results and discussion Five profiles of consumers were identified through the LPA, each one differently associated with the likelihood of investing in socially responsible products. The profile that best describes sustainable investors is characterized by high levels of knowledge toward SRI, risk appetite, positive attitudes on SRI, personal norms, perceived behavioral control, environmental concerns, and connectedness to nature. These findings suggest that non-financial aspects, namely psychological characteristics such as attitudes and personal values, play a key role in the decision to invest responsibly as well.